Antioxidant performance in droplet-stabilized oil-in-water emulsions. (March 2021) - Okubanjo, Sewuese S.; Ye, Aiqian; Wilde, Peter J.; Singh, Harjinder; Loveday, Simon M.
Abstract: Droplet-stabilized emulsions (DSEs) consist of large lipid droplets (the core) stabilized by smaller, protein-coated lipid droplets (the shell) and this structure effectively protects unsaturated lipids from oxidation. This study investigated and compared performance of an antioxidant (butylated hydroxyanisole- BHA) when incorporated either in shell droplets or in the core lipid of DSEs. Emulsions consisted of a core of polyunsaturated fatty acid (PUFA) oil emulsified with shell emulsions that contained either low (olive oil), or high (trimyristin) melting point lipids. Oxidation of emulsions was accelerated with a fluorescent lamp in the presence of ferrous iron (500 μmol/L) for eleven days, and PUFA oxidation was monitored via the formation of conjugated dienes, lipid hydroperoxides and hexanal. At 500 mg/kg BHA, oxidation was slower in DSEs with BHA-in-shell droplets than in emulsions with BHA-in-core PUFA oil, but the reverse trend was observed at 50 mg/kg BHA. Trimyristin DSEs processed below the shell lipid melting temperature gave the greatest oxidation resistance at both BHA levels. Results suggest that incorporating BHA into shell droplets of DSEs can be more effective than incorporating it into core PUFA oil, and BHA performance in DSEs may be dependent on its concentration, transfer mechanism and proximity to reaction sites. Highlights: Droplet-stabilized emulsions (DSEs) can incorporate antioxidants in core or shell. BHA antioxidant activity in DSEs depended on location and concentration. At 50 mg/kg, hexanal formation in DSEs was slower with BHA in the core. At 500 mg/kg, hexanal formation in DSEs was slower with BHA in the shell. DSEs with trimyristin shells resisted oxidation better than with olive oil shells.